A Microwave System For The Acid Dissolution Of Metal And Mineral Samples - Objective (The National Institute for Occupational Safety and Health (NIOSH), 1983)
Reduce the time, complexity and expense of dissolving metal and mineral samples in solution in preparation for chemical analysis. Approach In earlier research, the Bureau of Mines developed a rapid and inexpensive method for the dissolution of mineral and metal samples in plastic pressure bottles heated in a boiling water bath. Using this technique, samples could be prepared for chemical analysis in less than one hour compared with several hours by traditional dissolution methods (see Technology News No. 85, December 1980 for further details). By heating in a microwave oven, sample dissolution time can be reduced to approximately 5 minutes.